The Influence of Environmental Hygiene Factors and Water Consumption on Diarrhea: A Literature Review - Ramlah, Muhammad Rudi Asyari; Wahyuningsih, Nur Endah; Hanani, Yusniar (Universitas Khairun, 2024)
Diarrhea is a major cause of morbidity and mortality in all age groups and regions in the world. Environmental factors and drinking water are risk factors for diarrhea. it is important to examine the influence of environmental hygiene factors and drinking water on the incidence of diarrhea. Therefore, this study presents information regarding the influence of environmental cleanliness and drinking water on diarrhea by reviewing empirical studies in previous and current research. In order to identify the influence of environmental cleanliness and drinking water factors on the incidence of diarrhea, a review of literature collected from the PubMed, Scopus, Google Scholar databases in English and Indonesian was carried out. Literature taken from the last 10 years, namely from 2014 to 2024 and in the form of full text publications. Environmental sanitation factors and good drinking water play an important role in determining how susceptible a person is to gastroenteritis or diarrhea. The availability of clean drinking water is the most important factor in preventing diarrhea. Lack of clean water has emerged as one of the main factors causing diarrhea. Access to proper and clean drinking water is obtained from protected drinking water sources, including tap water (taps), public hydrants, public taps, water terminals, rainwater reservoirs or protected springs and wells, drilled wells/pumps that are at least a distance away 10 meters from waste disposal facilities can prevent diarrhea.